Novel structured ADAM17 small-molecule inhibitor represses ADAM17/Notch pathway activation and the NSCLC cells’ resistance to anti-tumour drugs - Chi, Meng; Jie, Yamin; Li, Ying; Wang, Duo; Li, Man; Li, Dan; E, Mingyan; Li, Yongwu; Liu, Na; Gu, Anxin; Rong, Guanghua (Frontiers in Pharmacology, 2023)
The outcomes of current treatment for non-small cell lung cancer (NSCLC) are unsatisfactory and development of new and more efficacious therapeutic strategies are required. The Notch pathway, which is necessary for cell survival to avert apoptosis, induces the resistance of cancer cells to antitumour drugs. Notch pathway activation is controlled by the cleavage of Notch proteins/receptors mediated by A disintegrin and metalloproteinase 17 (ADAM17); therefore, ADAM17 is a reliable intervention target for anti-tumour therapy to overcome the drug resistance of cancer cells. Compound 2b, a novel-structured small-molecule inhibitor of ADAM17, was designed and developed and its therapeutic efficacy in NSCLC was assessed via multi-assays. A lead compound for a potential inhibitor of ADAM17 was explored via pharmacophore modelling, molecular docking, and biochemical screening. It was augmented by substituting two important chemical groups (R1 and R2 of the quinoxaline-2,3-diamine [its chemical skeleton]); subsequently, serial homologs of the lead compound were used to obtain an optimized compound (2b) with high inhibitory activity compared with leading compound against ADAM17 to inhibit the cleavage of Notch proteins and the accumulation of the Notch intracellular domain in the nuclei of NSCLC cells. The inhibitory activity of compound 2b was demonstrated by quantitative polymerase chain reaction and western blotting. The specificity of compound 2b on ADAM17 was confirmed via point-mutation. Compound 2b enhanced the activation of antitumor drugs on NSCLC cells, in cell lines and nude mice models, by targeting the ADAM17/Notch pathway. Compound 2b may be a promising strategy for NSCLC treatment.